2019
DOI: 10.1016/j.ijbiomac.2019.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on properties of starch films obtained from potato, corn and wheat using 1-ethyl-3-methylimidazolium acetate as plasticizer

Abstract: Starch films are gaining attention as substitutes of synthetic polymers due to their biodegradability and low cost. Some ionic liquids have been postulated as alternatives to glycerol, one of the best starch plasticizers, due to their great capacity to form hydrogen bonds with starch and hence great ability of preventing starch retrogradation and increasing film stability. In this work, [emim + ][Ac-]-plasticized starch films were prepared from potato, corn and wheat starch. The effect of starch molecular stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(31 citation statements)
references
References 64 publications
1
30
0
Order By: Relevance
“…The observed functional groups con rm the characteristic of starch-based plain bioplastics, as evidenced by Patnaik, et al [29], Amin, et al [30] and Domene-López, et al [31].…”
Section: Corn Starch-based Plain Bioplastic and Lcnf Reinforced Bioplasticssupporting
confidence: 75%
“…The observed functional groups con rm the characteristic of starch-based plain bioplastics, as evidenced by Patnaik, et al [29], Amin, et al [30] and Domene-López, et al [31].…”
Section: Corn Starch-based Plain Bioplastic and Lcnf Reinforced Bioplasticssupporting
confidence: 75%
“…170 Additionally, ILs can act simultaneously as a plasticizer and conductive agent. 10,160,161,169,171 Recently, Zhang et al 11 found that starch could be straightforwardly processed into optically transparent electro-conductive films by compression molding in aqueous [Emim][OAc] at a relatively mild temperature (55 or 65 °C), much lower than those commonly used in biopolymer melt processing (typically over 150 °C) (Fig. 13).…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…A greener and more feasible way to produce a quantiable amount of HAp from Moringa leaves would be by supplementing the extracts with wastes from potatoes, almonds, and other vegetables with high phosphate content. [197][198][199] Shaltout et al analyzed the content of Catha edulis (C. edulis) by getting rid of the organic contents of the plants through a higher calcination process. The inorganic products of the leaves and stalks were identied to contain a quantiable amount of calcium hydroxyapatite aer employing characterization techniques, such as FTIR, XRD, and thermal analysis (TGA, DTG, DSC).…”
Section: Nature Of Templating Agents and Possible Applications Of Resmentioning
confidence: 99%